Gas6/TAM Signaling Components as Novel Biomarkers of Liver Fibrosis. (8th September 2019) - Smirne, Carlo; Rigamonti, Cristina; De Benedittis, Carla; Sainaghi, Pier Paolo; Bellan, Mattia; Burlone, Michela Emma; Castello, Luigi Mario; Avanzi, Gian Carlo
Abstract : Liver fibrosis consists in the accumulation of extracellular matrix components mainly derived from activated hepatic stellate cells. This is commonly the result of chronic liver injury repair and represents an important health concern. As liver biopsy is burdened with many drawbacks, not surprisingly there is great interest to find new reliable noninvasive methods. Among the many are new potential fibrosis biomarkers under study, some of the most promising represented by the growth arrest-specific gene 6 (Gas6) serum protein and its family of tyrosine kinase receptors, namely, Tyro3, Axl, and MERTK (TAM). Gas6/TAM system (mainly, Axl and MERTK) has in fact recently emerged as an important player in the progression of liver fibrosis. This review is aimed at giving an overall perspective of the roles played by these molecules in major chronic liver diseases. The most promising findings up to date acknowledge that both Gas6 and its receptor serum levels (such as sAxl and, probably, sMERTK) have been shown to potentially allow for easy and accurate measurement of hepatic fibrosis progression, also providing indicative parameters of hepatic dysfunction. Although most of the current scientific evidence is still preliminary and there are no in vivo validation studies on large patient series, it still looks very promising to imagine a possible future prognostic role for these biomarkers in the multidimensional assessment of a liver patient. One may also speculate on a potential role for this system targeting (e.g., with small molecule inhibitors against Axl) as a therapeutic strategy for liver fibrosis management, always bearing in mind that any such therapeutic approach might face toxicity.